Survival Strategy Of Farmworkers "Oil Palm Harvesters " Of Bakti Makmur Hamlet, Riau Using SWOT Analysis - Ginting, Loise Chisanta; Ritonga, Fajar Utama; Sinaga, Randa Putra Kasea (Journal of Peasants' Rights, 2024)
Agricultural workers who harvest oil palm in Bakti Makmur Hamlet are not all formal sector workers, so their income fluctuates and there is a risk of work accidents when harvesting oil palm fruit. On the other hand, there is a phenomenon of oil palm harvester farm workers in Bakti Makmur Hamlet who are still able to meet basic needs and even provide school education facilities to their children. To overcome these problems it is necessary to know how the survival strategy of oil palm harvester farm laborers Bakti Hamlet, Riau. The Data obtained in the field were then analyzed to produce a conclusion by using the theory of survival strategy of Edi Suharto, namely, active strategy, passive strategy, network strategy. The results found by the researchers is the community of Dusun bakti makmur village, riau do starategi survival according to Edi Suharto as a whole is an active strategy to improve the quality of production to increase income such as gardening, bedagang or even selling, looking for other jobs and involving families to work, passive strategy of frugal lifestyle that is clothing, food, Board, Education, health and network strategy is to establish relationships with the social environment such as owed to neighbors or stalls and receive assistance such as zakat or sacrificial offerings of love and farm laborers oil palm harvesters in Dusun bakti makmur riau village have patron and client relationships. Â